Recovery of neuronal and network excitability after spinal cord injury and implications for spasticity - D'Amico, Jessica M.; Condliffe, Elizabeth G.; Martins, Karen J. B.; Bennett, David J.; Gorassini, Monica A. (Frontiers in Integrative Neuroscience, 2014)
The state of areflexia and muscle weakness that immediately follows a spinal cord injury is gradually replaced by the recovery of neuronal and network excitability, leading to both improvements in residual motor function and the development of spasticity. In this review we summarize recent animal and human studies that describe how motoneurons and their activation by sensory pathways become hyperexcitable to compensate for the reduction of descending and movement-induced sensory inputs and the eventual impact on the muscle. We discuss how replacing lost patterned activation of the spinal cord by activating synaptic inputs via assisted movements, pharmacology or electrical stimulation may help to recover lost spinal inhibition. This may lead to a reduction of uncontrolled activation of the spinal cord and thus, improve its controlled activation by synaptic inputs to ultimately normalize circuit function. Increasing the excitation of the spinal cord below an injury with spared descending and/or peripheral functional synaptic activation, instead of suppressing it pharmacologically, may provide the best avenue to improve residual motor function and manage spasticity after spinal cord injury.